Natural History of Cryptosporidiosis in a Birth Cohort in Southern India. (24th December 2016) - Kattula, Deepthi; Jeyavelu, Nithya; Prabhakaran, Ashok D; Premkumar, Prasanna S; Velusamy, Vasanthakumar; Venugopal, Srinivasan; Geetha, Jayanthi C; Lazarus, Robin P; Das, Princey; Nithyanandhan, Karthick; Gunasekaran, Chandrabose; Muliyil, Jayaprakash; et al.
Abstract : In an Indian birth cohort, we demonstrate a high and early burden of cryptosporidiosis by polymerase chain reaction and serology. Reinfection was common and infections clustered in a subset of children. Prior infection provided some protection against subsequent infection, but not disease. Abstract: Background: Cryptosporidium is a leading cause of moderate to severe childhood diarrhea in resource-poor settings. Understanding the natural history of cryptosporidiosis and the correlates of protection are essential to develop effective and sustainable approaches to disease control and prevention. Methods: Children (N = 497) were recruited at birth in semiurban slums in Vellore, India, and followed for 3 years with twice-weekly home visits. Stool samples were collected every 2 weeks and during diarrheal episodes were tested for Cryptosporidium species by polymerase chain reaction (PCR). Serum samples obtained every 6 months were evaluated for seroconversion, defined as a 4-fold increase in immunoglobulin G directed against Cryptosporidium gp15 and/or Cp23 antigens between consecutive sera. Results: Of 410 children completing follow-up, 397 (97%) acquired cryptosporidiosis by 3 years of age. PCR identified 1053 episodes of cryptosporidiosis, with an overall incidence of 0.86 infections per child-year by stool and serology. The median age for the first infection was 9 (interquartile range, 4–17) months, indicating early exposure. Although infections were mainly asymptomatic (693 [66%]), Cryptosporidium was identified in 9.4% of diarrheal episodes. The proportion of reinfected children was high (81%) and there was clustering of asymptomatic and symptomatic infections ( P < .0001 for both). Protection against infection increased with the order of infection but was only 69% after 4 infections. Cryptosporidium hominis (73.3%) was the predominant Cryptosporidium species, and there was no species-specific protection. Conclusions: There is a high burden of endemic cryptosporidiosis in southern India. Clustering of infection is suggestive of host susceptibility. Multiple reinfections conferred some protection against subsequent infection.